BALANCING SUGAR AND STRAIN: LIVING WITH TYPE 1 DIABETES AND CHRONIC KIDNEY DISEASE - ST, Shaidatul; Abdullah, RA Raja; AH, Ghozali; CM, Choo; HL, Khoo (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Effective glycaemic control is essential in the type 1 diabetes mellitus (T1DM) to prevent both acute and chronic complications of the disease. This case explores the challenges faced in daily glucose regulation and highlights the critical role of tight glycaemic control in ensuring long term health outcomes for individuals living with the disease. CASE A 13-year-old male arrived at the emergency department in impending diabetic ketoacidosis (DKA). He was diagnosed with T1DM at the age of 3, though his antibody work-up was negative. His medical history revealed poor adherence to medical appointments and treatment, with multiple hospitalizations for DKA between the ages of 3 and 10. At 11 years old, he was completely lost to follow-up and was managing his insulin doses independently, without proper blood sugar monitoring. After 2 years without medical supervision, he was admitted with disseminated methicillin-sensitive Staphylococcus aureus (MSSA) infection, bilateral renal abscesses and stage 3a chronic kidney disease. His HbA1c at the time of admission was 14%. CONCLUSION This case highlights the serious consequences of poor glycemic control in T1DM. Persistent hyperglycemia and inadequate disease management likely contributed to immune dysfunction, heightened infection risk and progressive kidney damage, ultimately leading to his critical condition. Consistent diabetes management and early medical intervention are essential to prevent such life-threatening complications.